Hegemoni Kelas Menengah Atas Pada Buku Teks: Studi Analisis Dominasi Kelas Atas Terhadap Kelas Bawah Pada Buku Teks TK B - Abdurrohman, Asep; Zulkilfi, Zulkifli; Maemunah, Maemunah (Universitas Muhammadiyah Tangerang, 2023)
This study aims to find out how far the upper middle class dominates the lower class and to find out and analyze the narratives built in textbooks when interacting with the lower class. This research uses qualitative research based on library research, where the source of data used as research material is Kindergarten B textbooks. The data is analyzed using content analysis, namely; pragmatic content analysis, semantic content analysis, and analysis of sign means. The results of the study show that the dominance of the upper middle class over the lower class is drawn through lifestyles, such as; vacation to the beach, sitting on soft sofa chairs, diving, and so on. The narrative developed in the Kindergarten B textbook focuses more on urban lifestyles and the balancing narrative that can fit into the upper and lower middle social class is not too significant. Or in another language not apple to apple. Keywords: Hegemony, Upper Middle Class, Textbooks